A bibliometric review on latent topics and research trends in the growth mindset literature for mathematics education - Xu, Xiaoyu; Zhang, Qiaoping; Sun, Jin; Wei, Yicheng (Frontiers in Psychology, 2022)
Embracing a growth mindset is essential to students’ academic improvement. This paper aims to better understand existing literature on the role and effects of the growth mindset in mathematics teaching and learning. It provides an updated perspective on the research regarding the growth mindset in mathematics education. The dataset comprises 85 journal articles published from 2012 to 2022 retrieved from the Web of Science (WOS) and Scopus databases. The current study applies a methodology based on bibliometric analysis techniques. The analysis reveals and corroborates several patterns in the research trends, journals, countries, and authors that have significant impacts on the research field. The findings show that the USA, the UK, and Norway are the most productive countries in publishing research on the topic. Moreover, the results of the thematic analysis indicate that the topics discussed among most of the articles in the dataset include engagement, implementation, persistence, children, fluid intelligence, and skills. The longitudinal trends in research themes based on study keywords illustrate an evolution in the research from the concept of mindsets to implicit theories with the growth mindset alongside academic achievement. Lastly, this study also provides an overview of the conceptual structure underlying studies on the growth mindset, which offers valuable insights into potential research topics for academics and practitioners seeking to explore the growth mindset in the future.